2021
DOI: 10.1210/clinem/dgab056
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic Causes in the Type 1 Diabetes Genetics Consortium Cohort: Low Genetic Risk for Autoimmunity in Case Selection

Abstract: Hypothesis About 1% of patients clinically diagnosed as type 1 diabetes have non-autoimmune monogenic diabetes. The distinction has important therapeutic implications but, given the low prevalence and high cost of testing, selecting patients to test is important. We tested the hypothesis that low genetic risk for type 1 diabetes can substantially contribute to this selection. Methods As proof of principle, we examined by exom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Currently it is suggested that genetic tests for MODY should be performed when paediatric diabetes is diagnosed, together with modest hyperglycaemia and absence of all four islet autoantibodies (antibodies against GAD, insulinoma antigen-2, zinc transporter 8 and insulin), but there is no standardised diagnostic algorithm [ 12 , 132 , 133 ]. At present, genetic tests for MODY are conducted with NGS methodology due to lower costs and increased diagnostic accuracy [ 134 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…Currently it is suggested that genetic tests for MODY should be performed when paediatric diabetes is diagnosed, together with modest hyperglycaemia and absence of all four islet autoantibodies (antibodies against GAD, insulinoma antigen-2, zinc transporter 8 and insulin), but there is no standardised diagnostic algorithm [ 12 , 132 , 133 ]. At present, genetic tests for MODY are conducted with NGS methodology due to lower costs and increased diagnostic accuracy [ 134 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…One patient was compound heterozygous at WFS1 , the gene mutated in Wolfram syndrome and also responsible for non-syndromic diabetes. WFS1 variants have been reported from India[ 22 ], China[ 12 , 31 ], Korea[ 20 , 32 , 33 ], Russia[ 6 ], and European ancestry[ 34 ]. Finally, one variant was identified in ZBTB20 , a transcription factor that regulates the function of beta cells and glucose homeostasis[ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPEN ACCESS of antibody-negative sibling pairs from the T1D Genetics Consortium, selected for low genetic risk for T1D [10], in whom we did not detect disease-causing variants in the known MODY genes.…”
Section: Trends In Geneticsmentioning
confidence: 95%
“…In recent 'agnostic' searches in the exomes of autoantibody-negative patients with a clinical diagnosis of T1D, recessive WFS1 variants were found causing diabetes only, with none of the other manifestations of Wolfram syndrome [9,10]. Such nonsyndromic cases had been previously reported but thought to be rare and confined to populations with high consanguinity or endogamy [11,12].…”
Section: Supporting Preliminary Evidencementioning
confidence: 97%